SHIFTING THE SYSTEM OF INDONESIAN WORD FORMATION; THE STUDY ON MORPHOLOGY AND SOCIOLINGUISTICS OF ACRONYMS, BLENDING, AND CLIPPING - M Zaim (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2017)
The general guidelines of Indonesian word formation as annexed in appendix II of the reference standard of the Indonesian Grammar has not yet accommodated the Indonesian word formation system used by the Indonesian speakers today. Meanwhile, a new system of word formation began to emerge and the old paradigm shift in conjunction with the development of science and technology, and the change of social, cultural, and political paradigm. As a result, the reference standard of Indonesian grammar is no longer adequate to understand the system of the formation of the new words. Morphological studies, which analyze the internal structure of the words can be used as a theoretical foundation to address the issues of the Indonesian word formation. From the other side, sociolinguistic studies, which analyze the link of language with the language speakers in the community, can give meaning to the word formation shift. This article discusses (1) the morphological shift of the Indonesian word formation system of acronyms, blending, and clipping, (2) the sociolinguistic functions of the word formation, and (3) the productivity of the word formation system. The study of the shift of word formation system revealed a shift in the way of thinking and the way of looking at social, cultural, and political problems of the Indonesian speakers nowadays. Keywords: word formation, language shift, morphology, sociolinguistics, blending, clipping, acronymPERGESERAN SISTIM PEMBENTUKAN KATA BAHASA INDONESIA:KAJIAN MORFOLOGIS DAN SOSIOLINGUISTIK AKRONIM, BLENDING, DAN KLIPING AbstrakPedoman umum pembentukan kata Bahasa Indonesia pada Lampiran II Tata Bahasa Baku Bahasa Indonesia belum mengakomodasi sistem pembentukan kata Bahasa Indonesia yang digunakan oleh penutur Indonesia saat ini. Sementara itu, sistem pembentukan kata baru mulai bermunculan menggeser paradigma lama bersamaan dengan perkembangan ilmu pengetahuan dan teknologi, serta perubahan paradigma sosial, budaya, dan politik. Akibatnya, standar acuan tata bahasa Indonesia sudah tidak memadai lagi untuk memahami sistem pembentukan kata baru. Kajian morfologi, yang menganalisa struktur internal kata dapat dijadikan landasan teoritis untuk mengatasi permasalahan pembentukan kata bahasa Indonesia. Dari sisi lain, kajian sosiolinguistik, yang menganalisa hubungan bahasa dengan penutur bahasa di masyarakat, bisa memberi makna pada pergeseran pembentukan kata ini. Artikel ini membahas (1) pergeseran morfologis sistem pembentukan kata dalam bahasa Indonesia pada bentuk akronim, blending, dan kliping, (2) fungsi sosiolinguistik dari pembentukan kata, dan (3) produktivitas sistem pembentukan kata. Kajian tentang pergeseran sistem pembentukan kata mengungkapkan adanya pergeseran cara berpikir dan cara melihat masalah sosial, budaya, dan politik para penutur Bahasa Indonesia saat ini.Kata kunci: pembentukan kata, pergeseran bahasa, morfologi, sosiolinguistik, blending, kliping, akronim